Esotericism in Contemporary Lithuanian Prose - Naikienė, Ieva (Respectus Philologicus, 2018)
This article focuses on esotericism in contemporary Lithuanian prose. For the revelation of this topic, Donaldas Kajokas’ novel Ežeras ir kiti jį lydintys asmenys (The Lake and Other Escort Members, 2003) and Jurga Ivanauskaitė’s novel Placebas (Placebo, 2012) have been chosen. The analysed writings reveal the point of view of contemporary Lithuanian writers about esoteric beliefs. In this article, esotericism is related with persons’ feelings but is excluded from occult and parapsychology fields such as alchemy, cabbala, Tarot, etc. This work focuses on the idea that an individual, who has only a few senses, cannot reach actuality. On the other hand, the possibility of acquiring those senses is not rejected. In addition, obtaining those senses would help to reach higher, over-sensational worlds and in that way to discover personal correlation with forms of multiple personal identities. This article establishes an idea that awareness of higher worlds/spheres unlocks the possibilities of revealing the main core of human (as micro-cosmos) and the Universe (as macro-cosmos). The possibility to perceive oneself as a micro-cosmos discloses not only personal identity, but also the value of Other’s entity and inevitable entities stratifying.
Keywords: Esoteric; Contemporary Lithuanian Prose; Personal Identity; Universe; Universe Core